High frequency electromagnetic field affecting living organism - Staniak, Dorota; Sokołowski, Krzysztof; Majcher, Piotr (Polish Journal of Public Health, 2009)
Electromagnetic field (EMF) is the area in which penetration of electric and magnetic energy is mutual. It is taking part in practically every field of our life. Natural electromagnetic field is produced by The Sun or The Earth, however artificially it comes into being as an effect of present civilization. Every year development of the technology delivers new EMF’s sources increasingly. Among the most widespread are transmission lines, which boosting majority of home devices. These devices are mostly sources of 50/60 Hz electromagnetic fields. Some of them like television or radio emit radiation with higher frequency. Universally used at present microwave cookers or cellular telephones work in microwave range, that is frequencies above 300MHz. High frequency electric field has found use in medicine, as a short-wave diathermy, microwave diathermy or d’Arsonval’s electricity, applied to many orthopedic, rheumatic or muscular diseases treatment.EMF emitted from ubiquitous sources affects living organisms.Mechanisms of this interactions and its harmful effect is not totally known. It is known that electromagnetic field can affect metabolic processes in cells and disturb their working and functioning. High frequency radiation range can lead to overheat tissues, which cause thermal effect (the hyperthermia) and every stress reactions for organism. There are some coverages that long-term exposition on EMF causes the development of neoplastic disease. However investigations in this subject are not unambiguous.